2012
DOI: 10.1590/s0103-636x2012000200012
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between different kinds of students' errors and the knowledge required to solve mathematics word problems

Abstract: The main objective of this research is to examine the relationship between different kinds of errors and the knowledge required to solve word problems in Arithmetic, Algebra and Geometry. Kinfong's and Holtan's framework supports the analysis of the errors, and Mayer's theory was implemented to understand the necessary knowledge for solving math word problems. The research methodology follows a semi-experimental method. Research tools comprise both a descriptive math test and a directed interview. The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…Selain itu, siswa juga akan mengalami kesulitan dalam menyelesaikan jenis soal tersebut, khususnya ketika mengubah soal tersebut ke dalam bentuk atau kalimat matematika, ketika soal tersebut melibatkan operasi pada variabel-variabel (Nursuprianah & Nisa, 2013). Dengan demikian, menyelesaikan soal cerita matematika merupakan suatu hal yang tidak mudah bagi siswa dan bahkan mereka menghadapi berbagai kesulitan ketika menyelesaikan soal tersebut (Haghverdi et al, 2012). Kesulitan yang dialami siswa dalam memecahkan masalah matematika berpotensi menyebabkan mereka melakukan kesalahan (Hadi et al, 2018;Rafi & Retnawati, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Selain itu, siswa juga akan mengalami kesulitan dalam menyelesaikan jenis soal tersebut, khususnya ketika mengubah soal tersebut ke dalam bentuk atau kalimat matematika, ketika soal tersebut melibatkan operasi pada variabel-variabel (Nursuprianah & Nisa, 2013). Dengan demikian, menyelesaikan soal cerita matematika merupakan suatu hal yang tidak mudah bagi siswa dan bahkan mereka menghadapi berbagai kesulitan ketika menyelesaikan soal tersebut (Haghverdi et al, 2012). Kesulitan yang dialami siswa dalam memecahkan masalah matematika berpotensi menyebabkan mereka melakukan kesalahan (Hadi et al, 2018;Rafi & Retnawati, 2018).…”
Section: Pendahuluanunclassified
“…Salah satu pertimbangan yang mungkin dapat digunakan adalah jenis-jenis kesalahan yang siswa lakukan ketika menyelesaikan soal cerita matematika. Ini sesuai dengan yang dikemukakan oleh Haghverdi et al (2012) bahwa salah satu pendekatan yang dapat digunakan oleh guru untuk memfasilitasi siswanya dalam proses menyelesaikan soal cerita matematika adalah melalui identifikasi terhadap kesalahan-kesalahan yang dilakukan oleh siswa dalam menyelesaikan soal tersebut. Sejalan dengan yang dikemukakan oleh Haghverdi et al (2012) tersebut, Pradini (2019) menyebutkan bahwa identifikasi dan analisis terhadap kesalahan yang dilakukan oleh siswa merupakan langkah awal untuk menentukan strategi yang tepat untuk mengatasi kesulitan siswa dalam menyelesaikan masalah matematika.…”
Section: Pendahuluanunclassified
“…Such parity effects have received little attention in WP research so far. Furthermore, it seems that most WPs, especially for children, contain single-digit numbers ; e.g., each answer was in the range of 1–9, e.g., in Lean et al (1990) , or Powell and Fuchs (2014) , only few use multi-digit numbers ( Haghverdi et al, 2012 ). In Nesher (1976) the range of numbers is smaller than 100, contained division two-digit numbers into one-digit number.…”
Section: Numerical Complexity and Numerical Studiesmentioning
confidence: 99%
“…In the study of van der Schoot et al (2009) the final answers were between 14 and 40, included no fraction, no negative number, no numerical value twice, and none of the possible answers resulted in another. However, different types of numbers were presented in WPs in some more studies: (i) fraction ( Raduan, 2010 ), (ii) whole number, (iii) decimal number ( Haghverdi et al, 2012 ); and their effect has been rarely investigated. Koedinger and Nathan (2004) found an effect for decimal numbers: “however we also observed a smaller situation facilitation effect whereby story performance was better than word equation performance under certain conditions: namely dealing with decimal numbers.”…”
Section: Numerical Complexity and Numerical Studiesmentioning
confidence: 99%
“…From this point of view, researchers conducted studies especially on arithmetic and algebraic word problems with students at various grade levels in order to understand students' difficulties and to overcome them. The results of these studies reveal that students had difficulties due to various reasons as (i) inadequate reading comprehension abilities (Björn et al, 2014;Erdem, 2016), (ii) the semantic and syntactic structure of statements in the problems (Bernardo, 1999;Çelik & Taşkın, 2015;Mellone et al, 2014), (iii) types of numbers used in the problem (Haghverdi, Semnani, Seifi, 2012;Raduan, 2010), (iv) types of required operation (De Corte & Verschaffel, 1987;Varol & Kubanç, 2015;Vicente, Orrantia, & Verschaffel, 2007), (v) presence of relevant and irrelevant statements of problems (Gürsoy et al, 2015;Wang et al, 2016), and (vi) types of representations given in the problem situation (Boonen et al, 2014;Canköy & Özder, 2011;Deliyianni et al, 2016;Göbel, Moeller, Pixner, Kaufmann, & Nuerk, 2014). In conclusion, these studies showed that there are many factors influencing students' word problem solving.…”
Section: Theoretical Background Word Problems and Multiple Representamentioning
confidence: 99%